2018
DOI: 10.1111/sms.13219
|View full text |Cite
|
Sign up to set email alerts
|

Activity behaviors in lean and morbidly obese pregnant women

Abstract: Interventions to increase physical activity in pregnancy are challenging for morbidly obese women. Targeting sedentary behaviors may be a suitable alternative to increase energy expenditure. We aimed to determine total energy expenditure, and energy expended in sedentary activities in morbidly obese and lean pregnant women. We administered the Pregnancy Physical Activity Questionnaire (nonobjective) and the Actical accelerometer (objective) to morbidly obese (BMI ≥ 40 kg/m²) and lean (BMI ≤ 25 Kg/m²) pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We classified these covariates as demographic or potential confounders that may affect BMI, or fertility status in the NHANES database. 2 , 18 , 19 , 24 , 27 , 28 They were derived from self-reported data, examination data. Covariates included: age (18–45 years), race/ethnicity (Mexican-American, Other Hispanic, Non-Hispanic White, Non-Hispanic Black, Non-Hispanic Asian, Other Race), educational attainment (Less than high school, High school, More than high school), marital status (Married or Living with partner, Living alone), ratio of family income to poverty (ratio of household income to poverty indicators 29 ), alcohol consumption (at least 12 drinks of alcoholic beverages in the last year), active smoking (at least 100 cigarettes/year), diabetes mellitus, hypertension, and prior pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…We classified these covariates as demographic or potential confounders that may affect BMI, or fertility status in the NHANES database. 2 , 18 , 19 , 24 , 27 , 28 They were derived from self-reported data, examination data. Covariates included: age (18–45 years), race/ethnicity (Mexican-American, Other Hispanic, Non-Hispanic White, Non-Hispanic Black, Non-Hispanic Asian, Other Race), educational attainment (Less than high school, High school, More than high school), marital status (Married or Living with partner, Living alone), ratio of family income to poverty (ratio of household income to poverty indicators 29 ), alcohol consumption (at least 12 drinks of alcoholic beverages in the last year), active smoking (at least 100 cigarettes/year), diabetes mellitus, hypertension, and prior pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…In the manuscript by Fazzi et al 1 entitled "Activity behaviors in lean and morbidly obese pregnant women," physical activity assessed by questionnaire and accelerometry was reported to be lower in pregnant women with morbid obesity compared to pregnant women of normal weight. Total daily energy expenditure, however, was higher in women with morbid obesity.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Despite the lower total activity counts, compared to women with normal weight, women with obesity were reported to have higher energy expenditure. 1 The authors suggest that larger observed energy expenditure in women with obesity is due to differences in energy efficiency related to "the work of breathing and moving," which cannot be inferred without objectively assessing energy expenditure. Although we agree that energy expenditure at rest or during activity is likely larger in women with obesity as compared to lean women, we argue that this observation is due to their increased body mass, and not to decreased energy or mechanical efficiency.…”
Section: Dear Editorsmentioning
confidence: 99%